Assessment of Serum Electrolytes in Patients of Chronic Obstructive Pulmonary Disease - Nitin Rathi (Asian Journal of Medical Research, 2018)
Background: The aim is to assess serum electrolytes in patients of chronic obstructive pulmonary disease. Subjects and Methods: One hundred twenty acute exacerbations of COPD patients and eighty stable COPD patients of both genders were recruited in the study. Assessment of serum sodium, serum potassium, serum chloride using direct ion selective electrode and serum magnesium, serum calcium using arsenazo dye was performed. Results: Group I comprised of 70 males and 50 females and group II comprised of 45 males and 35 females. The mean serum sodium level was 131.4 mmol/L in group I and 137.5 mmol/L in group II, serum potassium level was 3.42 mmol/L in group I and 3.96 mmol/L in group II, serum chloride level was 93.2 mmol/L in group I and 99.7 mmol/L in group II, serum calcium was 7.65 mmol/L in group I and 8.38 mmol/L in group II and serum magnesium level was 1.14 mmol/L in group I and 1.62 mmol/L in group II. The difference found to be significant (P< 0.05) (Table II, graph I). The The mean serum sodium level <135 mmol/L was seen in 64% in group I and 45% in group II and >135 mmol/L in 36% in group I and 55% in group II. The mean potassium level <3.5 mmol/L was seen in 53% in group I and 22% in group II and >3.5 mmol/L in 47% in group I and 78% in group II. The mean chloride level <98.0 mmol/L was seen in 60% in group I and 38% in group II and >98.0 mmol/L was seen in 40% I group I and 62% I group II. The mean calcium level <8.7 mg/dl was seen in 81% in group I and 69% in group II and >8.8 in 19% in group I and 31% in group II. The mean magnesium level <1.30 mmol/L was seen in 74% in group I and 14% in group II and >1.30 mmol/L in 26% in group I and 86% in group II. Conclusion: Acute exacerbation of COPD patients exhibited abnormal serum electrolyte levels such as serum sodium, potassium, chloride and magnesium. Therefore, careful evaluation of serum electrolytes is mandatory in COPD patients.